Effects of NWT-03, an egg-protein hydrolysate, on blood pressure in normotensive, high-normotensive and mild-hypertensive men and women: a dose-finding study. Issue 7 (9th May 2017) - Plat, Jogchum; Severins, Nadine; Morrison, Steve; Mensink, Ronald P.
Abstract: Angiotensin-converting enzyme (ACE) inhibitors are important agents in blood pressure (BP) management. It was recently shown that the egg-protein hydrolysate NWT-03 inhibited ACE in Zucker diabetic fatty rats. We therefore designed a dose-finding study to assess the effects of 1, 2 and 5 g NWT-03 on daytime, 36-h, and night-time systolic and diastolic BP (SBP and DBP) in ninety-two generally healthy subjects with normal BP ( n 29), high-normal BP ( n 34) or mild hypertension ( n 29). The study had a cross-over design with six treatment arms (1 g NWT-03 or placebo in period 1 and placebo or 1 g NWT-03 in period 2, 2 g NTW-03 or placebo in period 1 and placebo or 2 g NWT-03 in period 2, or 5 g NTW-03 or placebo in period 1 and placebo or 5 g NTW-03 in period 2). A comparable number of subjects from each BP class were included in each study arm. Duration of both treatments in each arm was 7 d, separated by 5-d wash-out periods. BP was measured with an ambulatory BP monitor before and after the treatments. In mild-hypertensive subjects, 2 g NWT-03 significantly decreased daytime SBP (7·9 mmHg; P =0·006), daytime DBP (4·2 mmHg; P =0·009), 36-h SBP (6·9 mmHg; P =0·015) and 36-h DBP (3·5 mmHg; P =0·035) compared with placebo subjects. In addition, in mild-hypertensive subjects, 5 g NWT-03 significantly decreased night-time SBP (14·8 mmHg; P =0·008) and night-time DBP (8·4 mmHg; P =0·020) compared with that in placebo subjects. To conclude, we found that 2 g NWT-03 lowered daytime and 36-h BP in subjects with mild hypertension, and 5 g NWT-03 lowered night-time BP in subjects with mild hypertension. As no dose–response relationship was evident, these results should be interpreted with care, and additional studies are needed.